Fatigue Life Analysis of the Plastic Helical Gear and Steel Worm Transmission Mechanism - Liu Ganhua; Wang Qi; Tang Naifu (Jixie chuandong)
The rapid development of polymer materials has promoted the trend of plasticization of metal gears in medium and low load gear transmissions. Plastic helical gears are often used to replace metal worm gears in the worm and helical gear transmission, but the performance of metal and plastic materials is quite different, which leads to complex damage forms of plastic helical gears and the result that fatigue life is difficult to predict. To solve this problem, based on the Hertz contact theory and the relative coordinate method formed in the aerospace field, the multi-body dynamics software RecurDyn is used to establish the rigid-flexible coupling dynamic model to obtain the transient stress value of the plastic helical gear and then it is used as the load input value of the plastic helical gear in the Durability module. The relationship between POM gear fatigue life and contact stress amplitude in German plastic gear standard VDI 2736 is used to obtain the S-N curve of the plastic helical gear, and then the fatigue life of the plastic helical gear is studied based on the stress time history life calculation criterion. The accuracy of the analysis model is verified by the fatigue bench experiment, which provides a theoretical basis for the subsequent research on the fatigue life of plastic gears.